The Impact of government policy on private car ownership in Ireland - Hennessy, Hugh; TOL, RICHARD S. J. (Economic & Social Studies, 2011)
We construct a model of the stock of private cars in the Republic of Ireland. The model distinguishes cars by fuel, engine size and age. The modelled car stock is built up from a long history of data on sales, and calibrated to recent data on actual stock. We complement the data on the number of cars with data on fuel efficiency and distance driven ??? which together give fuel use and emissions ??? and the costs of purchase, ownership and use. We use the model to project the car stock from 2010 to 2025. The following results emerge. The 2009 reform of the vehicle registration and motor tax has led to a dramatic shift from petrol to diesel cars. Fuel efficiency has improved and will improve further as a result, but because diesel cars are heavier, carbon dioxide emissions are reduced but not substantially so. The projected emissions in 2020 are roughly the same as in 2007. In a second set of simulations, we impose the government targets for electrification of transport. As all-electric vehicles are likely to displace small, efficient, and little-driven petrol cars, the effect on carbon dioxide emissions is minimal. We also consider the scrappage scheme,which has little effect as it applies to a small fraction of the car stock only.
Keywords: Car ownership; Transport regulation; Transport policy